A Robust Hybrid of SnO2 Nanoparticles Sheathed by N‐Doped Carbon Derived from ZIF‐8 as Anodes for Li‐Ion Batteries. Issue 4 (22nd February 2017) - Yang, Dong‐Hui; Zhou, Xianlong; Zhong, Ming; Zhou, Zhen; Bu, Xian‐He
Abstract: A stable structure is critical for SnO2 ‐based materials to achieve high performance as anodes for lithium‐ion batteries because of the huge volume change during cycling. Herein, to address this issue, a hybrid of SnO2 nanoparticles implanted into porous N‐doped carbon frameworks with rich voids was fabricated via facile pyrolysis of a kind of zeolitic imidazolate frameworks, ZIF‐8, and vapor deposition of tetraphenyltin. This rationally designed material could effectively prevent the structural degradation due to the expansion and contraction during cycling, and exhibited remarkable Li storage performance. This anode material delivered a high reversible capacity of 1029.2 mA h g −1 at 100 mA g −1 and 445.0 mA h g −1 at a high rate of 5000 mA g −1, as well as stable cyclic performance of 667.1 mA h g −1 at 500 mA g −1 after 200 cycles. Importantly, the well‐defined architecture of the hybrid was retained after long charge/discharge cycles. Abstract : A hybrid material of SnO2 ‐based N‐doped carbon architectures with robust structures is prepared for lithium‐ion battery anodes. The well‐optimized hybrid nanostructure effectively prevents the structural degradation caused by the expansion and contraction during cycling, and therefore exhibits high specific capacity, good cycling stability and rate capability.